The impact of purchasing and Early Supplier Involvement (ESI) in a manufacturing firm - Abdul Hamid, Abu Bakar; Krishnapillai, Gengeswari (Universiti Teknologi Malaysia, 2006)
Globalization has caused increasing competitive pressures to manufacturers worldwide such as rapid technological development, increasing level of end-product complexity, shorter product life cycle and lead time, clock speed competition, and increased outsourcing. Thus, early supplier involvement (ESI) in new product development is becoming vital to manufacturing industry in developing competitive advantage, ever since manufacturing sector is the forerunner of the economic growth in Malaysia. This paper examines ESI in four building blocks of design, procurement,supplier, and manufacturing requirements, through the use of in-depth case study on a German based company. The objectives of the research are to study the supplier involvement in the mutual inclusive building blocks of ESI conceptual framework, to identify the factors that lead companies to implement ESI, and to analyze the impacts of ESI implementation. In addition, barriers to the effective ESI implementation includes suppliers are not allowed to involve in the process of the production at the final stage,and suppliers being not cooperative and slow in delivery. The critical factors that attract ESI implementation are to create strategic partnership with robust supply base, in which to produce best qualities with continuous cost cutting improvements, more dependent on suppliers to meet increasing competition and close collaboration between buying firm and suppliers. The findings revealed that the company is less actively in practicing ESI, in approaching suppliers and sharing information on design manufacturability and cost improvement, as it gives great impact on purchasing decision to accommodate effective and efficient supply on parts and components. The case study highlights the early supplier involvement during new product development, which is served as a valuable benchmark and guidelines for practitioners.